Hubungan Kejadian Stunting dengan Perkembangan Anak Usia 24-59 Bulan di Desa Wangen Polanharjo - Lilik hartati; Astri Wahyuningsih (INVOLUSI: Jurnal Ilmu Kebidanan, 2021)
Stunting is a condition of failure to thrive in children under five years of age, so that the child is too short for their age, but only appears after 2 years of age. The incidence of stunting in Indonesia is quite high, namely 30.8% (11.5% very short and 19.3% short). One of the impacts of stunting is a decrease in cognitive development, motor skills and speaking skills, so that early detection of short stature is necessary in order to be given intervention as soon as possible. This type of research uses the correlation method. The population in this study were all stunting toddlers aged 24-59 months in Wangen Polanharjo Village for the period March 2020. The sampling technique in this study used a total sampling technique with a sample size of 30 stunting toddlers aged 24-59 months in Wangen Polanharjo Village. The results showed that 23 children (77%) were stunted under five with appropriate development (11 children (36.6%), doubted 11 children (36.6%), and 1 child (0.3%) deviation. Meanwhile, stunting under five with a very short category, namely 7 children (23%) showed development according to 1 child (0.3%), doubted 3 children (1.0%), and 4 children (13.3%) had deviation. The conclusion in this study is that there is a relationship between the incidence of stunting and the development of children aged 23-59 months in the village of Wangen Polanharjo with a value of p = 0.024 (p <0.05).